Short Communication Production of Lactic Acid from Corn Cobs Through Fermentation by Lactobacillus delbruekii - Ali, Zulfiqar; Anjum, Faqir Muhammad; Zahoor, Tahir (Biological Sciences - PJSIR, 2007)
Corn cobs were used as the source of red uci ng sugars for con version i nto lactic acid through fermentation by a local strai n of Lactobacillus defbruekii, under varyi ng parameters of ti me, temperature, pH and glucose concentration . The prod uction of lactic acid sign i ficant l y i ncreased wi th i ncrease i n pH, fermentation time and gl ucose concentration ( 1 -5%) and was sign i ficantly h i gh (8.40 g/1) at pH 6, wh i le significan tl y low (7.67 g/1) at pH 5.